Management of Hemorrhoid Rubber Band Ligation Complications: Massive Rectal Bleeding - Merter GÜLEN; Ahmet Cihangir EMRAL; Bahadır EGE (Namık Kemal Tıp Dergisi, 2024)

(untitled)
Aim: The aim of this study is to present rubber band ligation (RBL), which is one of the non-surgical treatment options in hemorrhoidal disease, its complications and management of massive rectal bleeding, which is an important complication due to its morbidity. Materials and Methods: Between 2018-2022, five hundred and sixty-four RBL was performed for stage 1-2 and 3 internal hemorrhoidal disease. Seventy two patients with previous anorectal surgery, pregnancy, chronic liver disease were excluded. Four hundred and ninety two patients were included in the study. All patients underwent detailed anorectal examination, in patients over 50 years were evaluated by colonoscopy. The demographic characteristics of the patients, the number of applied band ligation and complications (minor-major) were evaluated. Results: The mean age of the patients was 33.4±11 (18-65) years, 385 were male (78.3%) and 107 were female (21.7%). Thirty-nine patients (8%) had single band ligation, 448 (91%) patients had double band ligation and 5 patients had triple band ligation. After RBL minor complications (anal pain, vasovagal symptoms, minor rectal bleeding, urinary retention) developed in twenty patients (4%) and massive rectal bleeding developed in 4 (0.8%) patients as a major complication. Conclusion: Hemorrhoidal banding is a safe and effective method for treatment of hemorrhoidal disease. This study highlights a rare, life-threatening complication of RBL.